Robopostman 1 2 3

broken image


Return to the Lessons Index | Do the Lessons in Order | Print-friendly page

Shop Zinsser Bulls Eye 1-2-3 Interior/Exterior Multi-Purpose Water-Based Wall and Ceiling Primer (Gallon) in the Primer department at Lowe's.com. Zinsser® BULLS EYE 1-2-3® is a whole house, Universal interior/exterior, water-based stain-killing primer-sealer. 2 1 2 1 1 x y=1−x y x y support set Blue: subset of support set with y1−x (a). We find c by setting 1 = Z ∞ −∞ Z ∞ −∞ f(x,y)dydx = Z 1 0 Z 2 0 (cx2 + xy 3)dydx = 2c 3 + 1 3, so c = 1. Draw a picture of the support set (a 1-by-2 rectangle), and intersect it with the set (x,y): x + y ≥ 1.

Composition of Functions:
Composing Functions at Points
(page 2 of 6)

Sections: Composing functions that are sets of point, Composing functions at points, Composing functions with other functions, Word problems using composition, Inverse functions and composition

Suppose you are given the two functions f (x) = 2x + 3 and g(x) = –x2 + 5. Composition means that you can plug g(x) into f (x). This is written as '( fog)(x)', which is pronounced as 'f-compose-g of x'. And '( fog)(x)' means ' f (g(x))'. That is, you plug something in for x, then you plug that value into g, simplify, and then plug the result into f. The process here is just like what we saw on the previous page, except that now we will be using formulas to find values, rather than just reading the values from lists of points.

  • Given f(x) = 2x + 3 and g(x) = –x2 + 5, find (gof )(1).
  • When I work with function composition, I usually convert '( fog)(x)' to the more intuitive ' f (g(x))' form. This is not required, but I certainly find it helpful. In this case, I get:

      (gof )(1) = g( f(1))

    This means that, working from right to left (or from the inside out), I am plugging x = 1 into f(x), evaluating f(x), and then plugging the result into g(x). I can do the calculations bit by bit, like this: Sincef(1) = 2(1) + 3 = 2 + 3 = 5, and since g(5) = –(5)2 + 5 = –25 + 5 = –20, then (gof )(1) = g( f(1)) = g(5) = –20. Doing the calculations all together (which will be useful later on when we're doing things symbolically), it looks like this:

      (gof )(1) = g( f (1))
      = g(2( ) + 3) .. setting up to insert the original input
      = g(2(1) + 3)
      = g(2 + 3)
      = g(5)
      = –( )2 + 5 .. setting up to insert the new input
      = –(5)2 + 5
      = –25 + 5
      = –20

    Note how I wrote each function's rule clearly, leaving open parentheses for where the input (x or whatever) would go. This is a useful technique. Whichever method you use (bit-by-bit or all-in-one), the answer is:

      (gof )(1) = g( f (1)) = –20

Robopostman 1 2 3/4

I just computed (gof )(1); the composition can also work in the other order:

  • Given f(x) = 2x + 3 and g(x) = –x2 + 5, find ( fog)(1).
  • First, I'll convert this to the more intuitive form, and then I'll simplify:

      ( fog)(1) = f (g(1))

    Working bit-by-bit, since g(1) = –(1)2 + 5 = –1 + 5 = 4, and since f(4) = 2(4) + 3 = 8 + 3 = 11, then ( fog)(1) = f (g(1)) =f(4) = 11. On the other hand, working all-in-one (right to left, or from the inside out), I get this:

      ( fog)(1) = f (g(1))
      = f (–( )2 + 5) .. setting up to insert the original input
      = f (–(1)2 + 5)
      = f (–1 + 5)
      = f (4)
      = 2( ) + 3 .. setting up to insert the new input
      = 2(4) + 3
      = 8 + 3
      = 11

    Either way, the answer is: Copyright © Elizabeth Stapel 2002-2011 All Rights Reserved

      ( fo g)(1) = f (g(1)) = 11

A verbal note: 'fog' is not pronounced as 'fogg' and 'gof ' is not pronounced as 'goff'. They are pronounced as 'f-compose-g' and 'g-compose-f', respectively. Don't make yourself sound ignorant by pronouncing these wrongly!

As you have seen above, you can plug one function into another. You can also plug a function into itself: Corelcad 2017 5 – reasonably priced cad solution cost.

  • Given f(x) = 2x + 3 and g(x) = –x2 + 5, find ( fof )(1).
    • ( fof )(1) = f ( f (1))
      = f (2( ) + 3) .. setting up to insert the original input
      = f (2(1) + 3)
      = f (2 + 3)
      = f (5)
      = 2( ) + 3 .. setting up to insert the new input
      = 2(5) + 3
      = 10 + 3
      = 13

Robopostman 1 2 3 =
  • Givenf(x) = 2x + 3 and g(x) = –x2 + 5, find (gog)(1).
    • (gog)(1) = g(g(1))
      = g(–( )2 + 5) .. setting up to insert the original input
      = g(–(1)2 + 5)
      = g(–1 + 5)
      = g(4)
      = –( )2 + 5 .. setting up to insert the new input
      = –(4)2 + 5
      = –16 + 5
      = –11

In each of these cases, I wrote out the steps carefully, using parentheses to indicate where my input was going with respect to the formula. If it helps you to do the steps separately, then calculate g(1) outside of the other g(x) as a separate step. That is, do the calculations bit-by-bit, first finding g(1) = 4, and then plugging 4 into g(x) to get g(4) = –11.

<< PreviousTop |1 | 2 | 3 | 4 | 5|6| Return to IndexNext >>

Robopostman 1 2 3 =

Cite this article as:

Vmware fusion 7 0 1 2217440 download free. Stapel, Elizabeth. 'Composing Functions at Points.' Purplemath. Available from
https://www.purplemath.com/modules/fcncomp2.htm. Accessed [Date] [Month] 2016





broken image